The value of preoperative RDW for post-pancreatectomy haemorrhage and surgical prognosis in patients with pancreatic cancer: a retrospective study - Ting Niu; Yueying Wang; Liangliang Lu; Jialin Li; Tianhua Cheng; Yuanqiang Dai (BMC Cancer)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor, and only some patients can receive surgical treatment. Complex surgical procedures combined with various postoperative complications seriously affect the prognosis of patients. It is very important to use appropriate biomarkers to prevent and predict the occurrence of complications. On the basis of our previous attention to red blood cell distribution width (RDW), this study aimed to investigate the correlation between RDW and the prognosis of pancreatic cancer patients. Methods Patients who underwent elective radical resection of pancreatic tumors from January 2017 to June 2021 were retrospectively analyzed. Relevant clinical data were collected to evaluate the correlation between preoperative absolute RDW changes and post-pancreatectomy haemorrhage and clinical outcomes. Results A total of 2268 patients were analyzed. We found that the preoperative RDW, preoperative LMR, anesthesia method, operation method, preoperative jaundice, operation with NSAIDs, and intravenous administration in patients with PDAC were significantly correlated with the infusion of albumin and R colloidal/crystal and post-pancreatectomy haemorrhage (PPH). In addition, sensitivity analysis revealed that preoperative RDW was associated with 30-day survival (P = 0.026), whereas PPH had a significant effect on in-hospital outcomes (P = 0.002), 30-day outcomes (P < 0.001) and 90-day outcomes (P < 0.001). Conclusion The preoperative RDW may be a useful marker for predicting and evaluating PPH and short-term prognosis in patients with PDAC.